The determinants of parents' school choice between public and private schools: Case study of high schools in Ha Noi - Lương, Thị An (2020)
The purpose of study to find out the determinants of the school choice of parents between public and private schools (family income, parent educational status, assessment of information, …) under the context of Viet Nam recently. From the data estimation, further discussion and recommendation for educational reform is implemented.